Open Wall at Museum and Gallery Tuanku Fauziah (MGTF), Universiti Sains Malaysia (USM): An Art-Based Interventions as a Therapeutic Activity to Improve Well-Being During COVID- 19 Pandemic - Muhammad Jameel, Mohamed Kamil; Mohd Najib, Abdullah Sani; Hasnul Jamal, Saidon; Safinawati, Samsudin (Persatuan Muzium Malaysia, 2022)
People who are confined or isolated during the COVID-19 pandemic are more prone to feel anxiety, sadness, stress, fear, traumatic reactions, and grieving issues to various degrees. Given the fact that arts treatments have long been utilized to address a range of mental health issues, the MGTF organized Open Wall, an art-based intervention as a therapeutic activity for family members among academics, non-academic staff, and students at USM. A preliminary survey was conducted to assess the perceptions of participants below the age of 18 after doing the activity. The result of the study enables the identification and validation of potentials associated with art expression, mental health, and social well-being among the participants. The implication of this study will help to widen the gaze on the possibilities of Open Wall as a method of inquiry on how art can contribute towards improving mental health and well-being during COVID- 19 pandemic.